Role and Function of Human Resource Management on The Performance of Correctional Officers - Adila, Rachmad; Wibowo, Padmono (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Lack of understanding of the function of human resource management that affects correctional officers' performance at the Class IIB Detention Center, Demak. Therefore, research is needed to determine the inhibiting factors and strategies for improving officers' performance. This study uses a qualitative descriptive method with a case study approach. The research was carried out at the Class IIB Detention Center, Demak. Primary data were collected through interviews and observations with the Informants of the Head of Class IIB Detention Center Demak, the Head of the Detention Center Security Unit, the Head of the Detention Service Sub-Section and the Head of the Management Sub-Section. In comparison, secondary data collects the literature on HRM and employee performance. Data analysis uses the Miles and Huberman model, where the data and information obtained will be processed through data reduction, data presentation, and data analysis. The results showed that the factors for the lack of understanding of the HRM function were lack of training and compensation, lack of supporting facilities, increased workload, and decreased motivation and soft skills of correctional officers. Several management process concepts include PDCE (Plan, Do, Check, Evaluate) and PDCA (Plan, Do, Check, Action). However, the POAC concept is more widely used and applied because it is more suitable for each management level. Therefore, to improve the performance of correctional officers, a unique strategy is needed to be called POAC (Planning, Organizing, Actuating, and Controlling).